Answer:
can u ;ut it in english plzz
Step-by-step explanation:
A = b is given to us
Multiply both sides by c to get
a = b
a*c = b*c
The rule to multiply both sides by c is the multiplicative property of equality
Then on the right side, replace c with d. This replacement is possible due to the fact that c = d. This is using the substitution property.
So we go from
a*c = b*c
to this
a*c = b*d
Answer:
4 terms
Step-by-step explanation:
4is the number of variable terms that are in the expression 3x3y + 5x2 _ 4y + z + 9. The four variable terms in the expression are "xy", "x^2", "y" and "z"
Answer:
2,455
Step-by-step explanation:
Use PEMDAS to solve
First multiply 50x50, which is 2,500
50 x 50 + 60 - 105 becomes
2,500 + 60 - 105
Now to the addition or subtraction from left to right
2,560 - 105
2,455
Answer:
Hi! I hope this is correct please inform me if this is incorrect :)
a = 1 will have.
2a + 3 < 9 - 3a.
2a + 3 > 10 -3a.
3a - 2a + 1>2.
a = 2 will have
ANY others I did not include in a = 1 :)
Please once again tell me if this is incorrect.
Step-by-step explanation: